PERDA NOMOR 4 TAHUN 2019 SEBAGAI PERLINDUNGAN HUKUM ATAS KUASA DAN WEWENANG DESA PAKRAMAN - Franshima, I Made Dhima; Pramana, Gede Indra; Mahaswari Jayanthi, A.A. Sagung Mirah (Jurnal Nawala Politika, 2022)
This research explains the Bali Provincial Regulation Number 4 of 2019 in providing legal protection for the power and authority of traditional villages in Bali. The scientific framework used in this research, are the concept of Legal Protection in the context of rights and powers, followed by a study related to the Bali Provincial Regulation Number 4 of 2019. The research approach used is descriptive qualitative by presenting secondary data sources. Based on this, the authors get the results that the existence of the Bali Provincial Regulation Number 4 of 2019 has given recognition, strengthened the role, and position of traditional villages in Bali. The powers and authorities of customary villages protected in the regulation are; management of the territory, carrying out development, resolving customary cases including carrying out customary law, and carrying out awig-awig or customary village regulations.